Ísland - Best í heimi?: Can a critical web series provide meaningful discourse? - Peter Bergstedt 1979- (2017)
This project demonstrates how one person with no money, can inspire a national discourse in Iceland. It aims to do so through the production of a critical web series, a marketing plan intended to make each webisode go viral, which in turn should spark a cultivated online public debate. The web series is based partially on research and interviews, but also on an examination of Icelandic culture, history and the apparent crypto-colonial mindset of the common Icelander. Via the production of a pilot, and the help of a focus group, the rather rough tone of the web series is found. The single finalised webisode is a short, factual and humorous mashup video about the short comings of the Icelandic Student Loans, and it is optimised for maximum viral spread. An extensive SWOT analysis of the launch of the web series concludes, that even if you do everything right, there is no such thing as a guaranteed viral hit. You will always need a little luck, for everything to work as intended. But if you have that, then one person, with a fully researched and well developed message, could very well inspire a national discourse.